In C. elegans, high levels of dsRNA allow RNAi in the absence of RDE-4. - Jeffrey W Habig; P Joseph Aruscavage; Brenda L Bass (PLoS ONE)
C. elegans Dicer requires an accessory double-stranded RNA binding protein, RDE-4, to enact the first step of RNA interference, the cleavage of dsRNA to produce siRNA. While RDE-4 is typically essential for RNAi, we report that in the presence of high concentrations of trigger dsRNA, rde-4 deficient animals are capable of silencing a transgene. By multiple criteria the silencing occurs by the canonical RNAi pathway. For example, silencing is RDE-1 dependent and exhibits a decrease in the targeted mRNA in response to an increase in siRNA. We also find that high concentrations of dsRNA trigger lead to increased accumulation of primary siRNAs, consistent with the existence of a rate-limiting step during the conversion of primary to secondary siRNAs. Our studies also revealed that transgene silencing occurs at low levels in the soma, even in the presence of ADARs, and that at least some siRNAs accumulate in a temperature-dependent manner. We conclude that an RNAi response varies with different conditions, and this may allow an organism to tailor a response to specific environmental signals.